Diagnostic Validity of Kramer’s Scale as Compared to Total Serum Bilirubin Neonates with Hyperbilirubinemia - Siluwal, Nirmala; Joshi, Anish; Poudyal, Prithuja; Rana Magar, Sapana; Laxmi Tui Tui, Roshani (Annapurna Journal of Health Sciences, 2023)
Background: Neonatal Jaundice (NNJ) is a physiological condition characterized by increase in total bilirubin concentration in the blood. High levels can lead to brain damage that causes cerebral palsy, visual and hearing loss hence early detection and appropriate management of neonatal jaundice is very important in preventing kernicterus. Visual assessment of jaundice using Kramer’s scale has proved to be highly effective. The objective of this study was to validate the diagnosis of jaundice using Kramer’s scale. Methods: This hospital based study was done in 107 neonates delivered and diagnosed with neonatal jaundice at Dhulikhel Hospital. Visual assessment of jaundice was done by two observers, result compared with that of transcutaneous bilirubinometer and total serum bilirubin. Results: The result of the study showed that the sensitivity and specificity of the Kramer scale were 94.3% and 31.9% respectively with 40.2% positive predictability and 92% negative predictability value against the TSB measurement. Similarly, there was 83.8% sensitivity, 44.4% specificity, 81.7% positive predictability and 48% negative predictability against transcutaneous Bilirubinometer. Conclusion: Kramer’s scale has high sensitivity and low specificity as compared to total serum bilirubin and transcutaneous bilirubinometer. Therefore it can be used as an alternative method to assess bilirubin level if there is no facility for total serum bilirubin (TSB) and Transcutaneous Bilirubinometer (TcB) measurement.